EKSPLORASI UTILITAS WEB 2.0 UNTUK MENUNJANG PROSES BELAJAR MENGAJAR DI PERGURUAN TINGGI - Bambang Supradono (MEDIA ELEKTRIKA, 2011)
Platform Web 2.0 utilities are websites that are colaburative, interactive, allowing users not only to read information but also to post information and interact with others. These tools offer new opportunities for designing instruction for heightened student engagement, particularly inlearning. This paper is a very practical introduction to using common Web 2.0 tools including wikis, blogs, social media, and social bookmarking sites etc. Sample assignments developed and used by the author or described in the literature are described. These assignments are adaptable for use in a variety of disciplines. Wikis are very useful for group work. Blogs can be used effectively for journals and independent studies. Social bookmarking can enhance organization and sharing of professional web resources. Specific tips for setting up and working with the sites are given as well as recommended resources including handouts and videos that introduce the sites. Other types of Web 2.0/social networking sites with promise for use in higher education, such as multimedia production sites, are briefly described and specific sites recommended.Keywords: Web 2.0 Technologies, Higher Education Teaching, Interactive Websites